2019
DOI: 10.1590/1516-4446-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among patients with presumptive pulmonary tuberculosis in Rio de Janeiro, Brazil

Abstract: Objective: To estimate the prevalence of major depressive episode (MDE) in patients with presumptive pulmonary tuberculosis (pre-PTB, defined by cough lasting ⩾ 3 weeks) and compare it between patients with pulmonary tuberculosis (PTB) and without PTB. Methods: Patients with pre-PTB (n=260) were screened for depression using the Patient Health Questionnaire (PHQ-9). Those individuals with scores ⩾ 10 were subsequently assessed with the depression module of the Mini International Neuropsychiatric Interview (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
3
10
1
Order By: Relevance
“…That said, the PHQ-9 is one of the most widely used globally to screen for depression among TB patients. Compared to other studies using the PHQ-9 among TB patients, the prevalence of depression in our sample was lower than samples from Cameroon (25%) India (42%), Ethiopia (54%), Pakistan (56%), and Brazil (62%) (Mandaknalli and Giriraj, 2015;Amreen and Rizvi, 2016;Kehbila et al, 2016;Ambaw et al, 2017;Castro Silva et al, 2018) but higher than one study in Nigeria (6.2%) (Issa et al, 2009). Other global studies using Hospital Depression & Anxiety Scale found similarly high prevalence estimates for depression including 47% (India), 46% (Pakistan), and 43% (Ethiopia) (Husain et al, 2008;Duko et al, 2015;Kunal et al, 2016).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…That said, the PHQ-9 is one of the most widely used globally to screen for depression among TB patients. Compared to other studies using the PHQ-9 among TB patients, the prevalence of depression in our sample was lower than samples from Cameroon (25%) India (42%), Ethiopia (54%), Pakistan (56%), and Brazil (62%) (Mandaknalli and Giriraj, 2015;Amreen and Rizvi, 2016;Kehbila et al, 2016;Ambaw et al, 2017;Castro Silva et al, 2018) but higher than one study in Nigeria (6.2%) (Issa et al, 2009). Other global studies using Hospital Depression & Anxiety Scale found similarly high prevalence estimates for depression including 47% (India), 46% (Pakistan), and 43% (Ethiopia) (Husain et al, 2008;Duko et al, 2015;Kunal et al, 2016).…”
Section: Discussioncontrasting
confidence: 82%
“…Given the strong overlap of symptoms between TB and depression, particularly physical symptoms (e.g. changes in appetite, sleep, or energy level), it is not clear if it is even valid to use the same cut-off score used in validation studies among non-TB patients (Castro Silva et al ., 2018). Individuals with high scores on self-report measures of depressive symptoms and meet interviewer-rated psychiatric diagnostic criteria (true positives) differ in important ways from individuals who obtain similarly high scores on self-report measures of depressive symptoms but do not meet interviewer-rated criteria for a diagnosis of depression (false positives) (Gotlib et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for exclusion are presented in figure 1, with the most common being that mental health is not a primary outcome or that the study design does not meet the inclusion criteria outlined above. Included studies span multiple locations, including five in Asia, [36][37][38][39][40] three in South America, [41][42][43] one in Africa 44 and one across low-income and middle-income countries (LMICs). 45 Two studies were published in the 1980s 38 40 and the remainder within the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of 259 participants screened for depression, the prevalence among TB cases is 60.2% versus 62.1% in controls (crude OR=0.92, 95% CI 0.55 to 1.54, p=0.79), and of 159 who screened positive for depression, this diagnosis was confirmed in 59.5% of TB cases versus 50.9% of controls (crude OR=1.42, 95% CI 0.63 to 3.19, p=0.42). 41 Beyond depression, a case-control study in Salvador, Brazil considers common mental disorders (CMDs) more broadly, characterised by diverse depressive, anxiety or somatoform symptoms, and finds elevated odds of having TB among those with a CMD (adjusted OR=1.34, 95% CI 1.05 to 1.70). 42 A cross-sectional study among the homeless in Medellín, Columbia investigates the association between TB and various psychiatric illnesses, but finds that only dysthymia (persistent mild depression) and history of major depression are associated with TB, and only for dysthymia is this statistically significant in multivariate analysis (adjusted OR=2.54, 95% CI 1.10 to 5.86, p=0.028).…”
Section: Mood Disordersmentioning
confidence: 99%
“…Resources such as trained health professionals and medical supplies are essential for providing the added care in this integration model. For example, a nurse and 2 medical students were trained for the integrated programme as reported in a study by De Castro-Silva and colleagues in Brazil [ 61 ], and a designated team of pharmacists and physicians worked together to design an individualised pharmaceutical care plan for TB and DM in the study conducted in Malaysia by Gnanasan and colleagues [ 59 ]. De Castro-Silva and colleagues had further reported that certain tools such as the Patient Health Questionnaire-9 (PHQ-9), which was originally a self-administered questionnaire had required providers to administer due to the population’s low literacy rate, thus showing the need to train providers to offer tailored services based on requirements of the target population.…”
Section: Resultsmentioning
confidence: 99%